Regioselective synthesis of 6-nitroindole derivatives from enaminones and nitroaromatic compounds via transition metal-free C–C and C–N bond formation. Issue 7 (2nd February 2022) - Ge, Danhua; Sun, Li-Wen; Yu, Zi-Lun; Luo, Xin-Long; Xu, Pei; Shen, Zhi-Liang
Abstract : A simple and practical Cs2 CO3 -promoted method for the synthesis of 6-nitroindole derivatives from enaminones and nitroaromatic compounds has been developed. Abstract : Few methods are known for the synthesis of nitroindole derivatives. A simple and practical Cs2 CO3 -promoted method for the synthesis of 6-nitroindole derivatives from enaminones and nitroaromatic compounds has been developed. Two new C–C and C–N bonds were formed in a highly regioselective manner under transition metal-free conditions.